Regression analysis-based Chinese Olympic Games competitive sports strength evaluation model research - Tang, G.; Li, J. (The Open Cybernetics & Systemics Journal, 2015)
The paper mainly applies a weighted accumulative method to predict Chinese previous Olympic Games medals total amount and analyze golden medals total amount floating change rule. According to analysis, the paper thinks that Olympic Games medals change rule can be predicted from three aspects that are Chinese economic strength, number of Chinese participants and Chinese medals amount changes followed by time. And then it establishes planning model that targets at minimum error amount between predicted value and actual value, by virtue of previous Olympic Games medals data, applying regression equation method, it gets every influence factor correlations with amount of medals; through applying algebraic calculus, it solves every influence factors weights and then gets medals predicted formula. Use the prediction formula, it solves the amount of medals in 2012, and contrasts with actual amount of medals in 2012, tests formula accuracy. Input Olympic Games relevant prediction data in 2016 into formula, and solve Brazil Rio de Janeiro Olympic Games predicted medals amount.